NON-GENETIC FACTORS INFLUENCING REPRODUCTIVE TRAITS AND PRE-WEANING MORTALITY OF LAMBS AND KIDS UNDER SMALLHOLDER MANAGEMENT, SOUTHERN ETHIOPIA - G. Deribe; G. Abebe; A. Tegegne (Journal of Animal and Plant Sciences, 2014)
This study was conducted to evaluate effects of non-genetic factors on litter size, age at first parturition (AFP), parturition interval (PI), seasonality of parturition, and pre-weaning mortality rate of sheep and goats flock with 587 kids and 467 lambs owned by 60 households. The litter size, AFP and PI (months) of lambs were 1.52+0.04, 12.43+0.1, 9.19+0.08, respectively, while the corresponding values were 1.47+0.04, 11.95+0.13 and 9.05+0.08 for kids. The average pre-weaning mortality rate was 14.84 and 12.59% for lambs and kids, respectively. Ewes of parity three had (p <0.05) higher litter size than parity one. Does having parity four and five had (p <0.05) higher litter size than parity three while does and ewes having parity three had (p <0.05) higher litter size than parity one. Site and season influenced litter size (p <0.5) and pre-weaning mortality of (p <0.01) lambs and kids. Birth weight (p <0.05) and parity influenced (p <0.01) pre-weaning kid mortality. To exploit reproductive potential of dams and enhance rural income from small ruminants, improved management measures have to be warranted.
Keywords: Litter size; Kids; Lambs; Non-genetic factors; Parturition; Southern Ethiopia